THE DIGITAL ENVIRONMENT AND ADOLESCENT PSYCHE: PSYCHOLOGICAL AND BEHAVIORAL CHANGES ARISING FROM THE INFLUENCE OF SOCIAL NETWORKS - Haydarova Dilnoza Bakhtiyorovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This study investigated the impact of the digital environment, particularly social networks, on the adolescent psyche. The study involved 40 adolescents, analyzing the correlation between their level of social media use and their psychological state (depression, anxiety, and behavioral changes). The results indicated that excessive use of social media is associated with an increase in symptoms of Depression and Anxiety Disorder. Furthermore, cases of sleep disturbance, aggression, and social isolation were also observed among the adolescents.